Pengaruh Gaya Kepemimpinan, Komitmen Dan Budaya Organisasi Terhadap Kinerja Pengurus (Studi Kasus Pengurus IMADE Malang Periode 2020-2021) - M. Rifki Afif; Agus Widarko; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of leadership style, commitment, and organizational culture on the performance of the management, the population in this study were members of the Malang Student Association (IMADE), as many as 53 administrators with the determination of the sample using the saturated sampling formula so that 53 samples were obtained. The type of research used is aquantitative method with an explanatory approach. The data used are primary datausing a questionnaire technique. The data analysis method used is instrument test:validity test and reliability test, normality test, classical assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis test: simultaneous test, partial test and coefficient of determination. From the results of simultaneous research The results show that leadership style, commitment and organizational culture have a significant effect on the performance of the management, from the results partially the leadership style variable has a positive effect on the performance of the management, the variable of organizational commitment does not have a positive effect on the performance of the management, and organizational culture does not have a positive effect on the performance of the management. Keywords: Management Performance, Leadership Style, Commitment and Organizational Culture.